Optimisation of cardiac resynchronisation therapy device selection guided by cardiac magnetic resonance imaging: Cost-effectiveness analysis. (April 2020) - Crespo, Carlos; Linhart, Markus; Acosta, Juan; Soto-Iglesias, David; Martínez, Mikel; Jáuregui, Beatriz; Mira, Áurea; Restovic, Gabriela; Sagarra, Joan; Auricchio, Angelo; Fahn, Bernhard; Boltyenkov, Artem; et al.
Background: A recent study showed that the presence and characteristics of myocardial scar could independently predict appropriate implantable cardioverter-defibrillator therapies and the risk of sudden cardiac death in patients receiving a de novo cardiac resynchronisation device. Design: The aim was to evaluate the cost-effectiveness of cardiac magnetic resonance imaging-based algorithms versus clinical practice in the decision-making process for the implantation of a cardiac resynchronisation device pacemaker versus cardiac resynchronisation device implantable cardioverter-defibrillator device in heart failure patients with indication for cardiac resynchronisation therapy. Methods: An incidental Markov model was developed to simulate the lifetime progression of a heart failure patient cohort. Key health variables included in the model were New York Heart Association functional class, hospitalisations, sudden cardiac death and total mortality. The analysis was done from the healthcare system perspective. Costs (€2017), survival and quality-adjusted life years were assessed. Results: At 5-year follow-up, algorithm I reduced mortality by 39% in patients with a cardiac resynchronisation device pacemaker who were underprotected due to misclassification by clinical protocol. This approach had the highest quality-adjusted life years (algorithm I 3.257 quality-adjusted life years; algorithm II 3.196 quality-adjusted life years; clinical protocol 3.167 quality-adjusted life years) and the lowest lifetime costs per patient (€20, 960, €22, 319 and €28, 447, respectively). Algorithm I would improve results for three subgroups: non-ischaemic, New York Heart Association class III–IV and ≥65 years old. Furthermore, implementing this approach could generate an estimated €702 million in health system savings annually in European Society of Cardiology countries. Conclusion: The application of cardiac magnetic resonance imaging-based algorithms could improve survival and quality-adjusted life years at a lower cost than current clinical practice (dominant strategy) used for assigning cardiac resynchronisation device pacemakers and cardiac resynchronisation device implantable cardioverter-defibrillators to heart failure patients.